Hybrid extracellular matrix design for cartilage‐mediated bone regeneration. Issue 1 (31st January 2017) - Mikael, Paiyz E.; Kim, Hyun S.; Nukavarapu, Syam P.
Abstract: Recapitulating long bone repair through endochondral ossification (EO) is increasingly becoming a more popular approach. A successful EO Process depends greatly on the establishment of a healthy hypertrophic‐cartilage template (HCT). The aim of this work is to design a hydrogel system, which closely mimics the extracellular matrix of HCT. We examined the combinatorial effect of two commonly used hydrogels for bone and cartilage regeneration strategies, hyaluronan (HA) and fibrin (FB), to induce HCT formation. Hydrogel combinations were evaluated using a clinically relevant cell source, human bone marrow mesenchymal stem cells (hBMSCs). The results establish that with increasing HA (50–90%) the chondrogenic and its subsequent hypertrophy trend improved, with 70:30 HA:FB combination showing the highest and most uniform expression of chondrogenic and hypertrophic stage specific markers. This combination also showed superior support for cell micro‐aggregation and differentiation. Thus, 70:30 HA‐FB matrix demonstrated a healthy formation of chondrogenic and hypertrophic stages with rich stage‐specific ECM components. This study demonstrates that with the appropriate hydrogel design it is possible to develop effective tissue engineering therapies for bone defect repair and regeneration through endochondral ossification by establishing a healthy HCT. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 300–309, 2018.